Effect of calcination temperature on the thermo-structural behavior and morphology of natural clay for eco-friendly composite applications - Edi Syafri; Salman Salman; Jamaluddin Jamaluddin; Nasmi Herlina Sari; Suteja Suteja (Mechanical Engineering for Society and Industry, 2025)
Natural clay is a low-cost and abundant material with potential as a sustainable filler in composite applications. Although natural clay has been widely explored as a sustainable filler material, systematic studies correlating calcination temperature with simultaneous thermal, structural, and morphological evolution remain limited. This study aims to evaluate how different calcination temperatures affect the thermal, structural, morphological, and physical properties of natural clay to determine its suitability for eco-friendly composite use. Clay powders were thermally treated at 600 °C (CCB), 700 °C (CCG), and 800 °C (CCM), and comprehensively characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), and physical testing. The results indicate that increasing calcination temperature significantly enhances crystallinity, and thermal stability, with the CCM sample (800 °C) exhibiting the most pronounced improvements. The CCM sample, calcined at 800 °C, exhibited the highest crystallinity index (72%), the lowest water absorption, the most compact microstructure, and the highest bulk density (6100 ± 40 kg/m³). TGA revealed improved thermal resistance up to 600 °C, with increasing char residue values from 38.2% (raw) to 48.2% (CCM), indicating enhanced thermal stability. FTIR analysis confirmed the reduction of hydroxyl and carbonate groups, particularly in the CCM sample. SEM observations showed a transformation from porous, irregular morphologies in raw clay to dense and homogeneous particles after calcination. These findings confirm that high-temperature calcined clay, especially the CCM sample, presents excellent potential as a sustainable filler material for high-performance green composites.